Development and validation of a scale for streaming dependence (SDS) of online games in a Peruvian population - Sairitupa-Sanchez, Liset Z (2023)
“Background: Addiction to online video game streaming has become one of the most appealing ways to occupy leisure time and is one of the most popular activities. The satisfaction it provides and the time invested in it are two of the main reasons why it is preferred. However, despite the clear benefits that this activity offers, in some cases, excessive use can lead to personal and/or family problems or abuse. Objective: The objective of the study was to develop and validate a scale to measure potential traits of dependence on online game streaming. The participants were 423 Peruvian adults aged between 18 and 47 years (M = 22.87, SD = 5.02). The Streaming Dependence Scale (SDS) was developed based on a literature review, and exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted. Results: The scale showed adequate internal consistency (α, CR, ω, and H > 80). Confirmatory analysis confirmed the one-dimensional structure (χ2 = 10.250, df = 5; p = 0.068; CFI = 0.98, TLI = 0.96, RMSEA = 0.06, SRMR = 0.05). Conclusion: The brief SDS is a valid and reliable measure that can be used as a useful tool to identify and evaluate streaming dependence.“